Pro-poor service delivery and social identity: An experimental investigation - Ulrike Mueller (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
India addressed the requirement for pro-poor service delivery in rural regions by introducing decentralization and affirmative action policies. In order to measure the social preferences of local decision makers, we conducted field experiments which simulated the selection of needy beneficiaries for welfare schemes. While potential recipients with less land were clearly favoured, decision makers also allocated resources to recipients with whom they could identify in terms of caste, gender and political party affiliation. The findings imply that the allocation of resources was not only motivated by neediness, but also by in-group favouritism. However, social identity-based preferences carry the danger of exclusion in providing rural services to the poor.
Keywords: C93; D30; I38; O12; 330; decentralization reforms; service delivery; in-group favouritism; field experiment; India; Ländliche Armut; Öffentliche Sozialleistungen; Dezentralisierung; Feldforschung; Indien